National Constitutions in European and Global Governance : Democracy, Rights, the Rule of Law -- National Reports - Albi, Anneli; Bardutzky, Samo (T.M.C. Asser Press, 2019)
This two-volume book, published open access, brings together leading scholars of constitutional law from twenty-nine European countries to revisit the role of national constitutions at a time when decision-making has increasingly shifted to the European and transnational level. It offers important insights into three areas. First, it explores how constitutions reflect the transfer of powers from domestic to European and global institutions. Secondly, it revisits substantive constitutional values, such as the protection of constitutional rights, the rule of law, democratic participation and constitutional review, along with constitutional court judgments that tackle the protection of these rights and values in the transnational context, e.g. with regard to the Data Retention Directive, the European Arrest Warrant, the ESM Treaty, and EU and IMF austerity measures. The responsiveness of the ECJ regarding the above rights and values, along with the standard of protection, is also assessed. Thirdly, challenges in the context of global governance in relation to judicial review, democratic control and accountability are examined. On a broader level, the contributors were also invited to reflect on what has increasingly been described as the erosion or 'twilight of constitutionalism, or a shift to a thin version of the rule of law, democracy and judicial review in the context of Europeanisation and globalisation processes. The national reports are complemented by a separately published comparative study, which identifies a number of broader trends and challenges that are shared across several Member States and warrant wider discussion. The research for this publication and the comparative study were carried out within the framework of the ERC-funded project 'The Role and Future of National Constitutions in European and Global Governance. The book is aimed at scholars, researchers, judges and legal advisors working on the interface between national constitutional law and EU and transnational law. The extradition cases are also of interest to scholars and practitioners in the field of criminal law. Anneli Albi is Professor of European Law at the University of Kent, United Kingdom. Samo Bardutzky is Assistant Professor of Constitutional Law at the University of Ljubljana, Slovenia.
Keywords: Constitutional law -- European Union countries.; Droit constitutionnel -- Pays de l'Union européenne.; International law.; International criminal law.; Human rights.; Jurisprudence & general issues.; Constitutional & administrative law.; Law -- International.; Law -- General.; Law -- Constitutional.; Constitutional law; European Union countries